Comparative evaluation of the environmental impact of chemical methods used to enhance natural fibres for composite applications and glass fibre based composites. (15th April 2017) - George, Michael; Bressler, David C.
Abstract: Natural fibres have emerged as a lightweight, low cost, and comparable property-wise alternative to glass fibres in composites. In this communication, natural fibres enhanced by chemical treatments for composite applications were evaluated for their environmental impacts using SimaPro 8.0. Hemp fibres were treated with two novel sulfonic acid methodologies and compared to accepted methods for fibre enhancement in the literature (mercerization treatment, acetic and propionic anhydride treatment). The tested experimental methods had a comparably lower environmental footprint than the literature approaches. Also, when further compared to the industry standard (glass fibre), the methods were superior. In the end, when used to reinforce poly(lactic) acid (renewable polymer) and polypropylene (non-renewable polymer), the experimental treatments had less of an environmental burden. In summary, through assessment with established methodology and standardized assumptions, we have proven that natural fibres can be enhanced using sulfonic acids, at the same time producing fibres with similar properties, but lower environmental burden than the compared alternatives. Highlights: Environmental impacts of two methods for natural fibre enhancement are reported. Experimental methods had lower environmental impacts versus the literature methods. Polypropylene composites outperformed PLA based composites. Natural fibre composites were characterized with lower environmental impacts.